2006
DOI: 10.1002/eji.200535506
|View full text |Cite
|
Sign up to set email alerts
|

Circumventing tolerance at the T cell or the antigen‐presenting cell surface: Antibodies that ligate CD40 and OX40 have different effects

Abstract: An adjuvant can be defined as an agent that non‐specifically promotes the immune response to an accompanying antigen. Ligation of CD40 on the surface of the antigen‐presenting cell leads to upregulation of OX40 ligand which, in turn, ligates OX40 on the activated T cell resulting in prolonged T cell proliferation/survival, boosting the immune response. Thus agonistic anti‐CD40 and anti‐OX40 might be viewed as “adjuvant antibodies” and have been shown in diverse experimental systems to either boost immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…Naive OT-II cells are sensitive to PIT when pOVA is administered i.v. in PBS (21,22,24). We assessed therapeutic efficacy of PIT in AAI by administration of pOVA 2 d after Th2 cell transfer and 4 d before i.t.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Naive OT-II cells are sensitive to PIT when pOVA is administered i.v. in PBS (21,22,24). We assessed therapeutic efficacy of PIT in AAI by administration of pOVA 2 d after Th2 cell transfer and 4 d before i.t.…”
Section: Resultsmentioning
confidence: 99%
“…This is different from the clinical setting where established T-celldriven pathology, by definition, presents with an increased frequency of antigen-experienced T cells (23). We, and others, have previously shown that application of tolerogenic peptide induces naive CD4 + T cells to enter a brief but abortive phase of proliferation that is followed by their wide-scale apoptotic deletion (21,22,24). This is most likely the result of insufficient costimulation from the antigen-presenting cell in the absence of innate immune triggers (21,22,24).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…1), but had no effect on IL-2 production and enhanced IFN-␥ production (Fig. 2), suggesting that anti-CD40 signaling may generate additional cellular effects, such as triggering IL-12 production by APCs, thus allowing pathogenic T cell differentiation (32).…”
Section: Discussionmentioning
confidence: 98%
“…Co-administration of agonistic antibodies binding the co-stimulatory molecules CD40 or OX 40 at the time of PIT can prevent the induction of tolerance (substituting for the use of LPS). [32,33] This correlates with sustained T-cell numbers by driving the expression of anti-apoptotic molecules Bcl-2 and survivin in the responding T cells. These are dependent on OX 40 signaling, [34,35] which is mediated either directly by the anti-OX40 or indirectly by elevated OX40 ligand expression on the peptide-MHC-presenting APC, triggered by CD40 signaling driven by the anti-CD40.…”
Section: Mechanisms Of Pitmentioning
confidence: 99%